Spectrophotometric determination of morin in strawberries and their antioxidant activity - Pavun, Leposava; Janošević-Ležaić, Aleksandra; Uskoković-Marković, Snežana (Archives of Pharmacy, 2021)
Morin is one of the flavonoids with intensive antioxidant activity. With the aim to use its benefits on human health, there is an increasing trend to pay attention to its content in food or supplements. The simplicity and low cost of spectrophotometric determination based on the formation of a morin complex with Zn2+ ion (stoichiometric ratio 1 : 1), at pH 7.98 and 392 nm, give it an advantage over other methods that can be used for morin quantification. The concentration range over which the response was linear was 0.151 – 4.533 mg L-1. The limit of detection (LOD) and the limit of quantification (LOQ) were 0.030 mg L-1 and 0.092 mg L-1, respectively. The developed method was successfully applied for the determination of the morin content in strawberries. Additionally, the antioxidative abilities of strawberry extracts and morin, determined by DPPH and FRAP tests, were compared and discussed.